Educational Leadership for Alpha-Oriented Multidisciplinary Faculty: Enhancing Collaboration, Harmony, and Productivity in Higher Education Settings - ANANG FATMA T. JAWALI (Journal of Daoist Studies, 2026)
ABSTRACT. Despite the need for cooperation, managing interdisciplinary faculty that demonstrate alpha-oriented tendencies in higher education presents serious issues for educational leadership. By examining the containment and empowerment tactics used by academic administrators, this study closes a research gap. The study used an exploratory qualitative approach and conducted in-depth interviews with 25 academic leaders who were specifically chosen for the study. In order to investigate how leadership behaviors affect dominant personality traits, the data were examined using reflexive thematic analysis, which was framed by trait activation theory. The results show that structural mechanisms that eliminate human power and reduce territorial behavior, such as data-driven dashboards and shared governance, are crucial neutralizers. According to the study, the best approach for handling assertive faculty in terms of productivity is bounded autonomy, which is typified by collaborative project charters and high-trust models. Along with structural empathy interventions like story circles to lessen emotional exhaustion in distributed leadership environments, the need for epistemic translation to resolve disciplinary disagreements is also highlighted. The study comes to the conclusion that effective leadership may use prospective disruptors as catalysts for institutional innovation by transforming affective conflict into cognitive conflict.